(untitled) (Research, Society and Development, 2021)
The multiple ovulation and embryo transfer (MOET) is the most used biotechnology in commercial sheep herds to produce embryos, however, several factors can interfere with the success and financial viability of the technique. The objective of the work was to evaluate the impact of technical training on the costs and financial feasibility of biotechnology. The study was carried out over four years (2017-2020) in a commercial system, in the state of SP, Brazil. Dorper breed ewes (n=35) were submitted to the MOET program using a conventional protocol (256 mg FSH) for up to five times (n=65). Artificial insemination took place on day 16 by laparoscopy and embryos were surgically collected with transfer to recipients (n=140) five days later. Direct costs for carrying out the MOET, reproductive rates and financial results of the cabanha were raised. The average amount of total structures and embryos transferred per collection showed a significant difference between years (P<0.05), with no difference (P>0.05) in the rates of pregnancy, permanent and transient adherence of donors. The gross margin per pregnancy was negative only in the first year and increased substantially in the following years, stabilizing the annual variation between costs and value of animals. In conclusion, the technical training of the veterinarian over four years was able to reduce costs and increase the efficiency of MOET, making the use of the technique financially viable in a Dorper sheep herd, accelerating the genetic improvement in the herd.